Disability and Human Diversity: A Reinterpretation of Ẹni-òòṣà1 Philosophy in Yorùbá Belief - Omotade Adegbindin (Yoruba Studies Review)
As an exercise in African philosophy, this paper examines and demonstrates the limitations of the two popular extremes in disability studies, namely, the medical and social models of disability. While the former is essentialist in rendering disability as a fixed condition and as an individual problem to be confronted with medical intervention, the latter identifies it as a social problem that requires social intervention. The paper employs the methods of hermeneutics, critical and conceptual analyses to facilitate an understanding that, within the context of Yorùbá belief, disability goes beyond the realm of human beings and involves the active participation of Yorùbá deities, especially Òrìṣà-ńlá or Ọbàtálá. Consequently, it questions the assumptions associated with the recognition of the dichotomy between “normality” and “abnormality” and confronts the mystical and/or mythographic representation of ẹni-òòṣà or persons with disabilities with a view to offering new insights into how persons with disabilities ought to be conceptualized in order to promote their inherent human dignity.